DETEKSI CACING PITA (Taenia solium L.) MELALUI UJI FESES PADA MASYARAKAT DESA PURWOSARI KECAMATAN TORUE KABUPATEN PARIGI MOUTONG SULAWESI TENGAH - Nelky Suriawanto; Musjaya M. Guli; Miswan Miswan (Biocelebes, 2014)
This study is about incidence of pork-tapeworm (Taeniasolium L.) in Purwosari village entitled “Detection of pork-tapeworm (Taeniasolium L.) infecesof people and swine in Purwosari village, Torue, sub-district of Parigi Moutong in Central Sulawesi”. It was done over March and may, 2013. The goal of this research was to detect the tapeworm in feces of Purwosari village community. Observation was done based on kato-katz and direct slide methods. Stool sample were collect from 33 people, and from 33 swines. The result showed that pork-tapeworm was not detected from all sample. In addition, other worms i.e. Trichuristrichura, Ascarislumbricoides, Ancylostomaduodenale, grouped as Soil Transmited Helmin (STH), were detected from the sample. Based on these data, we recomend to the comunity to continue their hygiene in daily lifestyle. Keywords: Taenia solium L., Swine, Feces, Detection.